Risk factors and mortality of adults with lung cancer admitted to the intensive care unit - Lai, Chih-Cheng; Ho, Chung-Han; Chen, Chin-Ming; Chiang, Shyh-Ren; Chao, Chien-Ming; Liu, Wei-Lun; Wang, Jhi-Joung; Yang, Ching-Chieh; Cheng, Kuo-Chen (Journal of Thoracic Disease, 2018)
Background: This study aims to investigate lung cancer patients’ risk factors for: intensive care unit (ICU) admission, infectious complications and organ dysfunction in the ICU, and prognosis after ICU admission. Methods: The records of all patients with lung-cancer catastrophic-illness cards admitted to the ICU between 2003 and 2012 were reviewed. The primary endpoint was 1-year mortality. Results: We finally analyzed the records of index-date-, age-, and sex-matched ICU-admitted (ICU+) lung cancer patients (n=17,687) and ICU-non-admitted (ICU–) lung cancer patients (n=35,374). The overall 1-year mortality rate was significantly (P